Critical Pedagogy in Higher Education: EFL Teachers’ Perceptions and Classroom Applications - Adhikari, Devi Prasad; Pandey, Gopal Prasad (AMC Journal, 2024)
Critical Pedagogy (CP) is a radical approach in education that transforms English as Foreign Language (EFL) classrooms into a discursive, interactive, and dialogic platform for raising students’ voices. The practice of CP in the classroom helps teachers to patronize their students’ oppressive voices. This study explored the perceptions and practices of critical pedagogy among higher-level EFL teachers. This is a qualitative study. It comprises a small sample; representing each university-level EFL teacher from different five colleges in Dhading district in Nepal. We used semi-structured interviews to collect information. The findings indicate that EFL teachers teaching at higher levels in Nepal are aware of students’ voices. They are practicing CP in their classrooms although they do not sound principally knowledgeable on CP. The practices of CP have fostered classroom environments supportive of hearing students’ suppressive voices. The teachers exhibited a positive stance on the importance of students’ voices within the classroom, actively listening to students’ interactions and encouraging their critical involvement in classroom dialogues. More broadly, classroom attentions by teachers to individual students are required to better practice CP.